Comparison of sustainable community rating tools in Australia. (16th December 2015) - Xia, Bo; Chen, Qing; Skitmore, Martin; Zuo, Jian; Li, Mei
Abstract: The community is the basic unit of urban development, and appropriate assessment tools are needed for communities to evaluate and facilitate decision making concerning sustainable community development and reduce the detrimental effects of urban community actions on the environment. Existing research into sustainable community rating tools focuses primarily on those that are internationally recognized to describe their advantages and future challenges. However, the differences between rating tools due to different regional conditions, situations and characteristics have yet to be addressed. In doing this, this paper examines three sustainable community rating tools in Australia, namely Green Star-Communities PILOT, EnviroDevelopment and VicUrban Sustainability Charter (Master Planned Community Assessment Tool). In order to identify their similarities, differences and advantages these are compared in terms of sustainability coverage, prerequisites, adaptation to locality, scoring and weighting, participation, presentation of results, and application process. These results provide the stakeholders of sustainable community development projects with a better understanding of the available rating tools in Australia and assist with evaluation and decision making. Highlights: We conduct an overview of three popular sustainable community rating tools in Australia. We use a content analysis to identify differences, strengths and weaknesses of these tools. We make recommendations for the future improvements of these rating tools.